Hierarchical Cu2S hollow nanowire arrays for highly efficient hydrogen evolution reaction. Issue 10 (4th May 2021) - Xie, Ning; Ma, Dong-Dong; Wu, Yu-Lin; Wu, Xin-Tao; Zhu, Qi-Long
Abstract : A self-supported three-dimensional unique hierarchical Cu2 S hollow nanowire array nanostructure with excellent activity for the hydrogen-evolution reaction was synthesized in a facile and economical way. Abstract : Exploiting highly active and low-cost electrocatalysts based on earth-abundant elements for the hydrogen evolution reaction (HER) is an extremely desirable, but challenging task. Herein, we present a facile and economical two-step synthetic procedure to fabricate hierarchical Cu2 S hollow nanowire arrays implanted tightly on copper foam (Cu2 S HNAs-CF). Owing to the unique hierarchical hollow nanowire array nanostructure of a large surface area, copious active sites, easy mass/transport ability, and high conductivity, the as-synthesized hierarchical Cu2 S HNAs-CF electrode (as a self-supported electrode) shows excellent electrochemical HER activity with a low overpotential of 125 mV @ 100 mA cm −2 in an alkaline electrolyte, and ranks as the top HER electrocatalyst reported. Upon coupling with the ordered macroporous RuO2 (OMS-RuO2 ), the Cu2 S HNAs-CF‖OMS-RuO2 /CF pair shows excellent performance for overall water splitting, which is significantly superior to those of most reported electrocatalysts and the commercial system PtC/CF‖RuO2 /CF.